1995
DOI: 10.1037/0022-3514.68.4.632
|View full text |Cite
|
Sign up to set email alerts
|

Championship pressures: Choking or triumphing in one's own territory?

Abstract: s (1984) provocative, widely accepted analysis proposed that professional sports teams play unusually badly (choke) under the pressure created by their home fans and perform poorly in decisive home games of championship series. However, a reanalysis of the data, including the results of recent championships in baseball and basketball, finds no evidence of a home-field championship choke. The home field is an advantage, and the home team wins about as often late as early in championship series. Teams show an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
69
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 22 publications
6
69
0
1
Order By: Relevance
“…The striking similarity between the CUSUM charts for the two divisions and their change points provides evidence of some change in a determinant(s) of home advantage that is common to both divisions. This strong evidence of a change in home advantage is an important finding because other research has generally concluded that home advantage is relatively constant over time (Courneya & Carron, 1992;Schlenker et al, 1995). Few studies have explicitly addressed temporal changes in home advantage, although Clarke and Norman (1995) examined the home advantage of individual clubs in the English Football League from 1981 -82 to 1990 -91 and found a significant year effect -with home advantage about 10% higher than average in 1982, 1983 and 1985, and 10% lower in 1981, 1987 and 1989.…”
Section: Discussionmentioning
confidence: 91%
“…The striking similarity between the CUSUM charts for the two divisions and their change points provides evidence of some change in a determinant(s) of home advantage that is common to both divisions. This strong evidence of a change in home advantage is an important finding because other research has generally concluded that home advantage is relatively constant over time (Courneya & Carron, 1992;Schlenker et al, 1995). Few studies have explicitly addressed temporal changes in home advantage, although Clarke and Norman (1995) examined the home advantage of individual clubs in the English Football League from 1981 -82 to 1990 -91 and found a significant year effect -with home advantage about 10% higher than average in 1982, 1983 and 1985, and 10% lower in 1981, 1987 and 1989.…”
Section: Discussionmentioning
confidence: 91%
“…More generally, the pressure to live up to the high expectations of an external audience can produce the phenomenon of "choking under pressure" (Baumeister, Hamilton & Tice, 1985;Baumeister & Steinhilber, 1984;Schlenker, Phillips, Boniecki, & Schlenker, 1995a, 1995b. Insofar as positive stereotypes communicate group-based expectations, explicit awareness of those stereotypes may introduce the same psychological factors that undermine performance, such as test anxiety, as negative stereotypes.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments suggest that the increase in incentives may lead to arousal beyond an optimal level, and may result in explicit monitoring that can interfere with the activity itself. In other words, preoccupation with a reward may lead to pressure-induced performance decrements (Baumeister, 1984;Baumeister & Showers, 1986;Schlenker, Phillips, Boniecki, & Schlenker, 1995). Thus, in psychological terms, intrinsic motivation is expected to be high enough to produce steady effort even in the absence of financial rewards, and incentives are likely to reduce performance (Camerer & Hogarth, 1999).…”
Section: Incentives and Performancementioning
confidence: 97%